50 Risk of ventricular arrythmia in ajmaline testing: significant variation identified in safety profile of the two most prevalent infusion protocols. (October 2018) - Byrne, L; Crinion, D; Keelan, E; Keaney, J; Galvin, J; Mahon, N; McGorrian, C
Abstract : Introduction: Brugada syndrome (BrS) is a hereditary sodium channelopathy that can result in ventricular arrhythmia (VA) and death. Characteristic coved ST elevation in the early precordial leads is transient, most often precipitated by fever or sleep. Sodium channel blockers such as Ajmaline can unmask these changes. However, a widespread variation in infusion protocols is evident in BrS studies. The two most prevalent protocols originate from the BrS Consensus reports. A total dose of 1 mg/kg was originally infused at a rate of 10 mg/min, however the same dose can be given over 5 min using a newer protocol. Patients greater than 50 kg will therefore receive a faster rate. This is the largest study to date that has included both protocols to assess risk of VA. Methods: A review of consecutive ajmaline tests done in the Mater Hospital was undertaken over a ten-year period from March 2008. The initial protocol of 1 mg/kg infused at 10 mg/min was changed to 1 mg/kg over 5 min in December 2014. In August 2016, due to a perceived increased risk in VA, the original protocol was reinstated. High precordial lead position was used in the second and third intercostal spaces. Results: A total of 209 consecutive ajmaline tests were performed over the ten-year period. 166 were infused at the 10 mg/min rate and 43 at the 5 min rate. 3 patients developed VA, all of which received the 5 min protocol (p=0.0086) (Fisher's exact test). Two of these cases required electrical cardioversion and none had evidence of ischaemic heart disease. The weight (Kg)/dose (mg) for the three VA patients were 98, 90 and 71. Conclusion: In this study there was a significant increase in the rate of VA in patients who received the 5 min infusion. The test is terminated when diagnostic criteria is met, however a greater dose has already been given with the 5 min rate, which may explain the progression to VA. These findings are in keeping with the two largest studies that utilised either of these protocols and included VA rates. The first demonstrated that 9/503 (1.8%) positive tests in a group receiving the 5 min rate had VA, while the other study found that 0/89 positive tests in a group getting the 10 mg/minute rate had VA. Of note neither of these studies examined differences in the rate of infusion as a potentially confounding variable. This study is the first to demonstrate that these infusion protocols should not be considered as interchangeable in terms of safety profile. Figure 1 Discrepancies in the rate of ajmaline administration between 2 infusion protocols in one patient who had VA (weight 98 kg). Figure 2 ECG tracing of V1H showing normal sinus rhythm transitioning into type one Brugada pattern and ultimately ventricular fibrillation in a patient receiving the 5 min infusion rate.